2022
DOI: 10.3390/a15110409
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Shared Genetic Bases between Psychiatric Disorders, Cardiometabolic and Sleep Traits Using K-Means Clustering and Local Genetic Correlation Analysis

Abstract: Psychiatric disorders are among the top leading causes of the global health-related burden. Comorbidity with cardiometabolic and sleep disorders contribute substantially to this burden. While both genetic and environmental factors have been suggested to underlie these comorbidities, the specific molecular underpinnings are not well understood. In this study, we leveraged large datasets from genome-wide association studies (GWAS) on psychiatric disorders, cardiometabolic and sleep-related traits. We computed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This restriction was based on robust Mahalanobis distances of the principal components using the dist_ogk function of the R package bigutilsr (Prive et al, 2020b). Finally, as studies have demonstrated that both T2DM and psychiatric disorders, particularly ADHD, genetically correlate with body mass index (BMI) (Fanelli et al, 2022;Zammarchi, Conversano, & Pisanu, 2022), we assessed the potential confounding or mediating role of BMI genetic liability by repeating the main PRS analyses including as a covariate a polygenic score for BMI based on a GWAS on 700 000 individuals (Yengo et al, 2018). Similarly, as a proxy of genetic susceptibility to low socioeconomic status, we included as a covariate a polygenic score for educational attainment based on a GWAS conducted in 766 345 European-descent individuals (Lee et al, 2018).…”
Section: Secondary Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This restriction was based on robust Mahalanobis distances of the principal components using the dist_ogk function of the R package bigutilsr (Prive et al, 2020b). Finally, as studies have demonstrated that both T2DM and psychiatric disorders, particularly ADHD, genetically correlate with body mass index (BMI) (Fanelli et al, 2022;Zammarchi, Conversano, & Pisanu, 2022), we assessed the potential confounding or mediating role of BMI genetic liability by repeating the main PRS analyses including as a covariate a polygenic score for BMI based on a GWAS on 700 000 individuals (Yengo et al, 2018). Similarly, as a proxy of genetic susceptibility to low socioeconomic status, we included as a covariate a polygenic score for educational attainment based on a GWAS conducted in 766 345 European-descent individuals (Lee et al, 2018).…”
Section: Secondary Analysesmentioning
confidence: 99%
“…T2DM and psychiatric disorders are heritable conditions, which aggregate in families; results of epidemiological studies document familial aggregation, with higher risk in first-than in second-degree relatives of affected probands, both for T2DM (Hemminki, Li, Sundquist, & Sundquist, 2010;Liao et al, 2022) and for many psychiatric disorders, including obsessivecompulsive disorder (OCD), autism spectrum disorder (ASD), anorexia nervosa (AN), schizophrenia, and attention-deficit/hyperactivity disorder (ADHD) (Chen et al, 2017;Chou et al, 2017;Hansen et al, 2019;Pardue et al, 2014;Steinhausen, Jakobsen, Helenius, Munk-Jorgensen, & Strober, 2015). Genome-wide association studies (GWAS) have confirmed the polygenic nature of each of these conditions (Demontis et al, 2023;Grove et al, 2019;Strom et al, 2021;Trubetskoy et al, 2022;Watson et al, 2019;Xue et al, 2018), and studies using GWAS summary statistics have also demonstrated genetic overlap between T2DM and several psychiatric disorders; this includes genetic correlations of T2DM with ADHD and major depressive disorder (MDD) in the positive direction, and with OCD, AN, and to some extent also schizophrenia in the negative direction (Fanelli et al, 2022;Zammarchi, Conversano, & Pisanu, 2022). Since GWAS-based genetic correlations do not always reflect phenotypic association patterns, using other genetically informative study designs, such as family designs, can help triangulate evidence of how genetic as well as environmental factors contribute to the associations between T2DM and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 98%